In-depth assessment of work-related stress in a major company undergoing restructuring - Magrini, Andrea; Pelagalli, Maria Felicia; Pietroiusti, Antonio; Livigni, Lucilla; Guidi, Stefano; Moscatelli, Maurizia; Mascioli, Marco; D'Orsi, Fulvio; Zolla, Antonella; Bagnara, Sebastiano (La Medicina del Lavoro, 2015)
Background: An in-depth assessment of work-related stress was conducted in a major national telecommunications company undergoing major changes. The assessment was made on three homogeneous groups of workers and covered a large representative sample of the corresponding populations. Objectives: To identify the main sources of stress for the three populations of workers, stimulate a discussion on the possible corrective actions, and assess the impact of the on-going organizational changes on workers’ health. Methods: The assessment started with an analysis of the objective stress indicators listed in the INAIL (National Insurance Institute for Occupational Diseases and Accidents) Checklist. This was followed by a combination of qualitative and quantitative investigations on work context and tasks and on the subjective perceptions of workers, which were carried out by using: semi-structured interviews with management, field observations of work tasks, focus groups and questionnaires (GHQ-12, HSE Indicator Tool, ad-hoc questionnaire). Results: The assessment allowed identification of the critical areas to be addressed with specific interventions: relationship with the company, work performance, work organization, and equipment. Conclusions: the investigation allowed to identification of specific practical actions (improvement of technological tools; professional development through training courses) as well as strategic actions ( re-establish relationship of trust with the company) so as to mitigate the workers’ level of stress. Analysis of the results also showed that the three targeted populations differed in the degree of acceptance and understanding of the organizational changes.